Hypoglycemic effect hydroacetone extracts of treculia africana decne root and stem bark in alloxan-induced diabetic rats (2014)
The main objective of this study was to compare the hypoglycemic activity of ethylacetate soluble portion of aqueous acetone extract of the root bark (EtOAcfr TARB) and stem (EtOAcfr TASB) back of Treculia africana Decne in diabetic rats and also to characterize the ultraviolent and infrared spectra of an isolated constituent. Oral administration of the EtOAcfr TARB reduced fasting blood glucose level by 28.6% in 144hrs and 15.9% at 240 hrs in alloxan (100 mg/kg) induced rat of five groups (n=5), with the use of glucometer (one touch ultra-code 23) at predetermined intervals of time. Phytochemical screening showed little or no difference in the constituents of the stem and the root. This was also demonstrated in the TLC separation pattern of the extract. Indications from this study could suggest that Treculia africana could be a potential hypoglycemic herbal drug as both the stem and the root extracts showed a sustainable and better reduction of blood glucose level when compared with standard drug (glibenclamide, 0.5 mg/kg) at 144 hr. The activity appeared more in the root bark of the plant.